Literature Review Crop Modeling and Introduction a Simple Crop Model - Le Huu Phuoc; Irfan Suliansyah; Feri Arlius; Irawati Chaniago; Nguyen Thi Thanh Xuan; Pham Van Quang (Green Engineering Society, 2023)
Modeling science has been applied by many advanced countries in many fields, such as geology, meteorology, climate change, crop productivity, environment, erosion, and landslide. The crop model simulates the processes of agriculture. The writing of this article is descriptive qualitative using the Systematic Literature Review (SLR) method. So far, each model has its advantages and disadvantages but generally is based on the physiology of the growth and development of crops in relationship with soil, climate, solar radiation energy, and limiting factors to plant growth. There have been many models for rice that can forecast yield and biomass or predict future climate change dynamics. Meanwhile, many models such as DSSAT, AquaCrop, Oryza, APSIM, EPIC need more data to operate their modeling, which in many cases, data is not readily available. In this review, we would like to introduce the model “SIMPLE” which includes only thirteen parameters and four of which describe cultivar characteristics. Another advantage of “SIMPLE” is that it can be adapted for many crop species and added variable modules such as nutrient dynamics, water stress, temperature stress, or pests. It is entirely open source based on R programming, but limitations still exist that have been mentioned in the review.